Beyond teacher transmission and Googling information to more creative language learning - Hall, Stephen J. * (Sanata Dharma University Press, 2018)
As information is readily available online, students can Google and Google Translate perhaps challenging a teacher’s classroom role and language awareness. The safety of being a transmitter of knowledge and instructor may be threatened and classrooms could become fossilized as the instant nature of information grows. This paper will argue that by facilitating modern language learning we could also stimulate questioning. Tasks may need to include appropriate on line searching and a creative inquiry approach to using language. This suggests reworking teacher dominance into a facilitator’s role. Digital natives and the Facebook/Instagram/Snapchat generation may want a culture of learning which embraces information flows, while providing tools for English language learning and use in the modern era. Suggestions for engaging learners with contemporary techniques will be shared, even for classrooms in which there is not readily available connectivity.